Pengaruh Komisaris Independen, Komite Audit, dan Intellectual Capital Terhadap Kinerja Keuangan Perusahaan: Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclycal yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Hanif Bima Hanggara; Fauzan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of independent commissioners, audit committees, and intellectual capital on financial performance in consumer non-cyclical sector companies listed on the Indonesia Stock Exchange for the 2021–2023 period. This research uses a descriptive quantitative method with secondary data obtained from annual and financial reports. The sample consisted of 165 data points selected using a purposive sampling method. Data analysis was conducted using multiple linear regression with SPSS 25 software. The results show that independent commissioners do not have a significant effect on financial performance. Meanwhile, audit committees and intellectual capital have a negative and significant effect on financial performance. These findings imply that strengthening the role of the audit committee and optimizing intellectual capital management are crucial for enhancing corporate financial performance.